Trajetórias de Homens Negros no Magistério: experiências narradas - Paula, Cláudia Regina de (2006)
The present study aims at examining the life histories of black male teachers working in elementary schools. It was developed around the following questions: What´s the black male teacher´s role in an environment predominatly white and feminine such as the schools? How do these professionals side when it comes to questions related to power and domination in the schools´ daily life? Does he reproduce the historical male dominance in his workplace? Are they subject to prejudice and discrimination? How do they deal with such situations? How do they see themselves? Data for the study were collected through inerviews which tried to capture the the elements that influenced his career choices and the character permanent or transitory of such choices. In sum, we tried to understand the making of these men. The methodological approach comprised the use of questionares and interviews. The filed research took place Belfort Roxo city´s public school system. Besides the field research, the dissertation also encompasses theoretical studies about gender, education and racial relations in Brazil.